Pemertahan Bahasa Baku di Tengah Kemunculan Kosakata Gaul Pada Gen Z: Sebuah Analisis Sosiolinguistik - Siti Atiqah Qistina; Eva Nurmayani (STKIP Subang, 2026)
The era of digital hyperconnectivity has triggered a radical shift in language ecology, establishing internet slang as the primary lingua franca of Generation Z (Gen Z). This study aims to explore the processes, meanings, and subjective experiences of Gen Z in their efforts toward standard Indonesian language maintenance amidst the hegemony of internet slang. Employing a quantitative descriptive approach with a survey design, data were collected from 20 Gen Z university students through a linear scale questionnaire (1-4) measuring four sociolinguistic indicators. The results refute the assumption that Gen Z is losing its standard language competence. Findings reveal that although internet slang dominates their daily habits (mean = 3.14) and frequently triggers the phenomenon of